Dydaktyka online i semi-online: jak stosować technologie cyfrowe w nauczaniu filozofii i etyki - Nowak, Ewa (Filozofia Publiczna i Edukacja Demokratyczna, 2012)
Internet access and semi-online teaching methods seem to be useful in a scientific and technological education. How efficient they can be in a philosophical and sociomoral education? Experiencing of full inclusion and open discourse are preconditions of moral and democratic education. I show supporting opportunities for semi-online teaching by giving an exemple that is based o story from A. Schopenhauer.